(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fatmawati M, Suwanti LT, Mufasirin, Subekti DT, Ekawasti F, Lastuti NDR, Lamid M, Suprihati E, Effendi MH, Al-Arif A. 2023. Optimization of deoxyribonucleic acid extraction and polymerase chain reaction methods for gene detection of Toxoplasma gondii in goat milk. Biodiversitas 24: 5905-5911. Dairy goats (Capra aegagrus hircus) are intermediate hosts that transmit Toxoplasma gondii to humans through goat milk consumption. T. gondii can invade mammary glands and secrete into milk. The method of detecting gene of the T. gondii in milk is through a Polymerase Chain Reaction (PCR) test based on specific genes. The objective of this study was to compare the efficacy methods of the T. gondii molecular assay from the extraction, master mix for PCR assay, and primer that is possible to amplify the gene of T. gondii in goat milk for PCR assay. The research method for purification used flotation using concentrated sugar. This research compared the extraction kit from Kit Extraction 1 (K1), Kit Extraction 2 (K2), and Kit Extraction 3 (K3) with the extraction method listed in the brochure. Meanwhile, for the PCR assay, three types of master mix were used, including Master Mix 1 (M1), Master Mix 2 (M2), and Master Mix 3 (M3). The specific genes used included primers B1, ROP, GRA 1, GRA 7, BAG 1, and P30. Tris borate EDTA (TBE) or Phosphate Buffer Saline Solution (PBS) as buffer milk samples gave the same PCR test results. The results show that the principle of a flotation method test using PBS can be used to prepare the milk sample. The research showed that extraction kit 1 (K1) and extraction kit 2 (K2) gave positive results for the positive control. However, in terms of price, K2 is cheaper than K1. So, to optimize DNA extraction, K2 can be used. The master mix that can be used for PCR testing of milk samples is M1 because M1 gives positive results for positive controls and negative results for negative controls. Primers for optimal results used GRA 7 and B1 with denaturation temperature of 94°C, annealing at 56°C, and an extension of 73°C 33. This research concluded that the type of DNA extraction kit affects the PCR test results for detecting T. gondii in goat milk. It is necessary to optimize the type of master mix to be used in PCR testing and primers capable of amplifying the T. gondii gene.